Wavelet signatures of K-splitting of the Isoscalar Giant Quadrupole Resonance in deformed nuclei from high-resolution (p,p′) scattering off 146, 148, 150Nd - C.O. Kureba (Physics Letters B, 2018)
The phenomenon of fine structure of the Isoscalar Giant Quadrupole Resonance (ISGQR) has been studied with high energy-resolution proton inelastic scattering at iThemba LABS in the chain of stable even-mass Nd isotopes covering the transition from spherical to deformed ground states. A wavelet analysis of the background-subtracted spectra in the deformed 146, 148, 150Nd isotopes reveals characteristic scales in correspondence with scales obtained from a Skyrme RPA calculation using the SVmas10 parameterization. A semblance analysis shows that these scales arise from the energy shift between the main fragments of the K=0,1 and K=2 components. Keywords: 146, 148, 150Nd(p,p′), ISGQR K-splitting, Wavelet analysis, Characteristic energy scales, Semblance analysis